Simple ceramics hand-built pots for kitchen and garden - Richardson-Hyde, Dawna (Lothian Australian craft series., 1995)
Delightful, practical projects you can use in your house and garden. You don't need a potter's wheel, just access to a kiln. These desirable objects are all made with simple techniques such as slab building and drape moulding. Each step is clearly illustrated and most projects suggest variations on design and decoration. Projects include candlestick holders, spice jars, fruit bowls, garden screens, decorative spoons, bonsai planters and much more!